2020
DOI: 10.1038/s41564-020-0779-9
|View full text |Cite
|
Sign up to set email alerts
|

Large freshwater phages with the potential to augment aerobic methane oxidation

Abstract: There is growing evidence that phages with unusually large genomes are common across various microbiomes, but little is known about their genetic inventories or potential ecosystem impacts. In the present study, we reconstructed large phage genomes from freshwater lakes known to contain bacteria that oxidize methane. Of manually curated genomes, 22 (18 are complete), ranging from 159 kilobase (kb) to 527 kb in length, were found to encode the pmoC gene, an enzymatically critical subunit of the particulate meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 82 publications
(89 reference statements)
1
71
1
Order By: Relevance
“…An intriguing finding was the linkage of host family-specific viruses from two different geographical regions (Scotland and Sweden) and contrasting soil types (agricultural loamy-sand and permafrost peatland soils), from this study and that of Emerson et al 9 , respectively. In the latter study, 13 of 1,907 mVCs were predicted to have a methanotroph host, of which 9 were linked specifically to the Methyocystaceae .…”
Section: Supplementary Textmentioning
confidence: 52%
See 1 more Smart Citation
“…An intriguing finding was the linkage of host family-specific viruses from two different geographical regions (Scotland and Sweden) and contrasting soil types (agricultural loamy-sand and permafrost peatland soils), from this study and that of Emerson et al 9 , respectively. In the latter study, 13 of 1,907 mVCs were predicted to have a methanotroph host, of which 9 were linked specifically to the Methyocystaceae .…”
Section: Supplementary Textmentioning
confidence: 52%
“…There was a clear difference in the prediction of category-2 (‘likely’) and category-3 (‘possible’) mVCs associated with these two clusters. While category-3 viruses are often excluded prior to analysis of soil viromes 9 , CRISPR analysis demonstrated that one-third of linked mVCs were of the lowest category of confidence. It must be recognised that a proportion of the predicted category-3 mVCs in this study will not be derived from viruses, and clusters composed exclusively of category-3 mVCs without further validation (e.g.…”
Section: Supplementary Textmentioning
confidence: 99%
“…The ibpA/B genes have never been identified from genetic screens of hostfactors necessary for capsid morphogenesis, but sHSPs are encoded in the genomes of cyanophage infecting Synechococcus and Prochlorococcus groups (68, 69). Furthermore, a bacteriophage-encoded J-domain protein (Rki) has been identified in T4-related enterobacteriophage RB43 that interacts with E. coli J-domain interacting chaperone protein DnaK (HSP70) and stabilizes the σ 32 heat-shock response (70).…”
Section: Discussionmentioning
confidence: 99%
“…As a relatively reliable computational method for detecting bacteriophage-host association signals, the CRISPR spacer-based approach has been applied in many virome studies [10,14,[26][27][28]. A total of 7,075 CRISPR spacer sequences were identi ed from 393 representative MAGs covering a total of 24 phyla (Additional File 10: Table S6).…”
Section: Crispr-based Bacteriophage-host Link Eventsmentioning
confidence: 99%
“…Bacteriophages can affect the diversity and function of aquatic microbial populations through the incorporation and expression of auxiliary metabolic genes (AMGs). Currently, phage-encoded AMGs are reported to include multiple types of genes involved in not only main nutrient cycle pathways, such as carbon metabolism [12][13][14], nitrogen [15], phosphorus [16] and sulfur cycling [17,18], but also some speci c pathways, such as acetate fermentation [19], methane oxidation [14], nucleotide metabolism [20] and oxidative stress responses [21]. Taken together, these ndings imply that viral AMGs in uence most, if not all, pathways of microbial metabolism.…”
Section: Introductionmentioning
confidence: 99%